Anterior Cruciate Ligament Reconstruction Rehabilitation Clinical Practice Patterns: A Survey of the PRiSM Society. Issue 4 (20th April 2019) - Greenberg, Elliot M.; Greenberg, Eric T.; Albaugh, Jeffrey; Storey, Eileen; Ganley, Theodore J.
Background: Recovery after anterior cruciate ligament (ACL) reconstruction (ACLR) requires extensive postoperative rehabilitation. Although no ideal rehabilitation procedure exists, most experts recommend a fusion of time and strength and functional measures to guide decision making for activity progression during rehabilitation. This process is often directed by surgeon protocols; however, the adoption of contemporary rehabilitation recommendations among surgeons is unknown. Purpose: To understand the current landscape of surgeon practice as it relates to ACLR rehabilitation recommendations in adolescent athletes. Study Design: Cross-sectional study. Methods: An online survey was distributed among members of the Pediatric Research in Sports Medicine (PRiSM) Society in January 2017. The survey was designed to identify clinical practice patterns during 3 key transitional points of rehabilitation after ACLR: progression to jogging, modified sports activity, and unrestricted return to sports. Results: Responses from 60 orthopaedic surgeons were analyzed. While 80% of surgeons agreed upon initiating jogging within a 1-month range (3-4 months postoperatively), similar levels of agreement were only captured when including a wider 4-month (4-8 months) and 6-month range (6-12 months) for modified sports activity and unrestricted return to sports, respectively. All respondents (100%) reported using knee strength as a determinant to progress to modified sports activity; however, the mode of testing varied, with most using manual muscle testing (60%), followed by isokinetic (28%) or isometric (12%) testing. Most surgeons (68%) reported using some form of functional testing to return to modified sports activity, but the mode of testing and required progression criteria varied considerably among all reported testing procedures. The use of patient-reported outcome measures was limited to 20% of the sample, and no respondents reported using fear or self-efficacy questionnaires. Upon completion of rehabilitation, 73% recommended injury prevention programs, and 50% recommended the use of a functional ACL brace. Conclusion: Rehabilitation progression practices in adolescent athletes are variable and become more inconsistent as the time from surgery increases. While the majority of the sample considered strength and functional testing important, the mode of testing and criteria thresholds for activity advancement varied considerably.